Mr. Putter & Tabby : Clear the decks - Rylant, Cynthia; Howard, Arthur (Boston : Houghton Mifflin Harcourt, 2010)
To relieve the boredom of a long, hot summer, Mr. Putter and his cat Tabby join their fun-loving neighbor, Mrs. Teaberry, and her mischievous dog Zeke on an adventurous sightseeing boat cruise.
"Sandpiper."
Horn Book
School Library Journal
Wilson's Children
Christian Library, February 2011
Horn Book, May 2011
Keywords: Boats and boating -- Juvenile fiction; Cats -- Juvenile fiction; Neighbors -- Juvenile fiction; Old age -- Juvenile fiction; Summer -- Juvenile fiction; Boats and boating -- Fiction; Cats -- Fiction; Neighbors -- Fiction; Old age -- Fiction; Summer -- Fiction; Boats and boating -- Fiction; Cats -- Fiction; Neighbors -- Fiction; Old age -- Fiction; Summer -- Fiction; Readers (Publications)